Dapsone induced hypersensitivity syndrome: a case report - Kolli, Sarika; Suhagiya, Priyanka (International Journal of Basic & Clinical Pharmacology, 2020)
Dapsone is an anti-leprotic drug. It may cause a severe adverse effect known as dapsone hypersensitivity syndrome which involves fever, chills, rash, and internal organ involvement. We report a case of a patient who is 30 years old male presented with fever, skin desquamation, and hepatitis. The case is being reported to emphasize the need to diagnose and manage dapsone hypersensitivity syndrome.